ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL OPERASI HITUNG BENTUK ALJABAR DI SMPN 14 PONTIANAK - Saputra, Bernadictus Osorio; Halini, Halini; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to find out describing students' mistakes in solving the algebraic arithmetic operations in class VIII of SMPN 14 Pontianak. This research used descriptive qualitative method. Data collected using tests, interviews, and documentation. The subjects in this research were students of class VIII SMPN 14 Pontianak. The test results show that the mistakes made by students include concept errors, principle errors and careless mistakes. Concept errors include students wrong in adding up algebraic forms because they add up different terms. Principle errors include students using associative, distributive and operating positive and negative integers. Carelessness errors include students writing wrong signs, writing errors in problem solving and do not simplify the answers to the right form. Keywords: Algebraic Arithmetic Operations Students Mistakes,